Effects of Replacing Groundnut Meal with Cotton Seed Meal or Palm Kernel Meal on the Performance, Blood Metabolite and Cost on Return of Finishing Cockerels. (Global Journal of Science Frontier Research, 2017)
Three hundred day-old black Harco cockerel chicks were started on a standard fish meal diet containing 2.65 Kcal/g ME at 21% crude protein for the first four weeks. At the end of which one hundred and forty of the birds were allocated to another diet of 2.65 Kcal/g ME at same 21% protein but without fish meal. The remaining 160 birds were maintain alongside on a fish meal diet containing 2.65Kcal/g ME and 21% protein till they were eight weeks old. At the finisher phase the two set of birds were assigned to eight experimental rations in a 4×2 factorial design; differently maintained. The diets were a control which contain fish meal and groundnut meal (GNM) as the major protein source. The next had only GNM as the major protein source. In the next consecutive diets, one-third, two-third and all of the GNM protein contribution was replaced by corresponding protein value of cotton seed meal (CSM) and palm Kernel meal (PKM).
Keywords: cockerels; groundnut meal; cottonseed meal; palm kernel meal and fish meal